2018
DOI: 10.1016/j.trecan.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Trinucleotide Repeat Expansion Diseases, RNAi, and Cancer

Abstract: Summary Many neurodegenerative diseases are caused by unstable trinucleotide repeat (TNR) expansions located in disease-associated genes. siRNAs based on CAG repeat expansions effectively kill cancer cell lines in vitro through RNA interference (RNAi). They also cause significant reduction in tumor growth in a human ovarian cancer mouse model with no toxicity to the treated mice. This suggests that cancer cells are particularly sensitive to CAG TNR-derived siRNAs and explains a reported inverse correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 151 publications
(202 reference statements)
0
18
0
Order By: Relevance
“…CAG-repeat-containing mRNAs have been shown to induce sRNA formation and cellular toxicity via RNAi ( Bañez-Coronel et al, 2012 ). However, we recently reported that these sCAGs likely target fully complementary CUG containing repeat regions in the ORFs of genes critical for cell survival in an siRNA-like mechanism ( Murmann et al, 2018a ; Murmann et al, 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…CAG-repeat-containing mRNAs have been shown to induce sRNA formation and cellular toxicity via RNAi ( Bañez-Coronel et al, 2012 ). However, we recently reported that these sCAGs likely target fully complementary CUG containing repeat regions in the ORFs of genes critical for cell survival in an siRNA-like mechanism ( Murmann et al, 2018a ; Murmann et al, 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…They occasionally induce genomic instability leading to generation of SVs, including both pathogenic and adaptive copy number variations (CNVs). The most famous disease related to CNV of tandem repeats is triplet repeat disease, which is evoked by the expansion of arrays comprised of very short units, such as CAG, GAA, CGG, and CCG trinucleotides ( 7 ). In contrast, facioscapulohumeral muscular dystrophy is caused by the contraction of D4Z4 macrosatellite repeats comprised of a 3.3-kb unit harboring the DUX4 gene ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, they serve as genetic fingerprints; a consequence of their high mutation rate. In addition, microsatellites have a well-established role in diseases such as fragile X syndrome, spinocerebellar ataxias, myotonic dystrophy, Friedrich ataxia, and Huntington's disease [5, 6].…”
Section: Introductionmentioning
confidence: 99%